Pressure effect on electrical conductivity of hydrogen molecular solid: Quantum mechanical approach - Bag, Arijit (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Configuration Interaction method is used to calculate transfer integral of hydrogen molecular solid which is used to calculate its electrical conductivity. Using this newmethod we have calculated the transition pressure (2.8 Mbar) and critical density (1.302 gm/c3) of hydrogen molecular solids which is found in very good agreement with the experimental results and other theoretical calculations